COMMUNITY SERVICE IN OVERSEEING THE DEMOCRATIC PROCESS OF VOTING AT POLLING STATION 48 SALADARA CIREBON - Yusuf Safari; Asep Gunawan; Devi Yuliananda; Suhana Minah Jaya (Ann Publisher, 2024)
The People's Party, in choosing a candidate for its deputy, is rife with enthusiasm. Residents in every RT flocked to the nearest polling station according to its permanent voter list (DPT). This atmosphere will repeat once every five years. Each Polling Station brings its distinctive nuances that significantly give a different atmosphere in the life of the nation and state. This community service activity was carried out to oversee the democratic voting process at polling station 48 Saladara Cirebon City. The method used is observing and entering into democratic activities and encouraging democratic officials. The results showed that the election process at polling station 48 Saladara went smoothly. Activities begin H-1 before implementation by preparing chairs and tables. D-day at 06.00, Officers are ready to arrange the election logistics, and precisely at 08.00, The callfor the people to vote begins. At exactly 13:00, the voting process was closed, and there was a 1-hourbreak. At 14.00, start counting sura until 24.00. The sura box is guarded overnight to wait for thenext day to be picked up by the Exodus for the next counting process.